A density explanation of valence asymmetries in recognition memory - Alves, Hans; Unkelbach, Christian; Burghardt, Juliane; Koch, Alex S.; Krüger, Tobias; Becker, Vaughn D. (Memory & cognition, 2015)
The density hypothesis states that positive information is more similar than negative information, resulting in higher density of positive information in mental representations. The present research applies the density hypothesis to recognition memory to explain apparent valence asymmetries in recognition memory, namely, a recognition advantage for negative information. Previous research explained this negativity advantage on the basis of valence-induced affect. We predicted that positive information’s higher density impairs recognition performance. Two old-new word recognition experiments tested whether differential density between positive and negative stimuli creates a negativity advantage in recognition memory, over and above valence-induced affect. In Experiment 1, participants better discriminated negative word stimuli (i.e., less false alarms) and showed a response bias towards positive words. Regression analyses showed the asymmetry to be function of density and not of valence. Experiment 2 varied stimulus density orthogonal to valence. Again, discriminability and response bias were a function of density and not of valence. We conclude that the higher density of positive information causes an apparent valence asymmetry in recognition memory.